We will start with the known identity that


and assume for contradiction that $e=\frac pq$. Then we have that $p=qe$, where $p$ is an integer. So then $q!e$ is also an integer number (specifically $p(q-1)!$). This means that


Now, we can split this sum into two parts:

$$q!e=\sum_{n=0}^q \frac{q!}{n!}+\sum_{n=q+1}^\infty\frac{q!}{n!},$$

and note that each term in the first sum is an integer (because $n!|q!$ when $n\leq q$). On the other hand, in the second sum,


where there are $n$ terms in $q!(q+1)\cdots(q+n)$. This gives us our contradiction. Since the first sum in $q!e$ are all integers and the second sum is positive and less than 1, $q!e\notin\mathbb{Z}$ and thus $e$ is irrational.

I can't specifically say anything that's wrong with it, but I still don't feel good about it. In particular, I'm skeptical about rewriting $n!=q!(q+1)\cdots(q+n)$ when taking a sum to infinity, as well as the inequality, but I can't specifically say what might be wrong about it.


1 Answer 1


You should have written $$\sum_{n=q+1}^\infty \frac{q!}{n!} = \sum_{n=1}^\infty \frac{q!}{q!(q+1)\cdots(q+n)} \le \sum_{n=1}^\infty \frac{1}{(q+1)^n} = \frac{1/(q+1)}{1 - 1/(q+1)} = \frac{1}{q} < 1$$ since $q > 1$. Note the index of summation shifts. The argument you made is sound.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.